GNQ-209P Mutation in Metastatic Uveal Melanoma and Treatment Outcome - Nagla Abdel Karim; Ihab Eldessouki; Ahmad Taftaf; Deeb Ayham; Ola Gaber; Abouelmagd Makramalla; Zelia M. Correa (Case Reports in Oncological Medicine)
Metastatic prognosis in uveal melanoma is assessed by gene expression profiling (GEP) testing of the tumor cells, usually obtained by fine needle aspiration (FNA). GEP has demonstrated high accuracy in distinguishing class I and II tumors, both having different metastatic potential. Transcriptomic studies identified distinct mutations including somatic mutations in GNAQ and GNA11, detected in more than 80%, and contribute to the upregulation of the mitogen-activated protein kinase (MAPK) pathway and the development of uveal melanoma (UM). The role of these mutations in treatment selection and possible benefit from targeted therapy are somewhat unclear. However, until the discovery of novel agents, local versus systemic therapies remain options for treatment that can still be considered for disease control in certain cases. We report a series of patients with metastatic UM with distinct mutational profiles. One had significant liver metastases with proven GNQ-209P mutation on tissue biopsy while peripheral blood molecular profiling did not show these mutations. The other three cases had no GNQ-209P mutation. All cases received nab-paclitaxel (Abraxane) as a treatment drug, and we record their responses to treatment and their molecular-profiling results.